Social Media Metrics as Indicators of Repository Impact - Kim Holmberg; Stefanie Haustein; Daniel Beucke (Purdue University Press, 2022)
The altmetrics movement has introduced user counts generated from social media platforms as crowdsourced filters of the relevance of scientific content and thus as broader and timelier measures of research impact than citations (Priem, Taraborelli, Groth & Neylon, 2010). Various altmetrics, or social media metrics, might be useful for repositories to measure the visibility of their contents on social media and bookmarking platforms complementing download and citation metrics. This is particularly true for preprint repositories because activity on social media can keep up with the acceleration of the publication life cycle: opposed to citations, social media activity is visible in real time right after online availability. For example, tweets to scientific papers have been shown to peak shortly after online availability (Eysenbach, 2011; Shuai, Pepe & Bollen, 2012; Haustein, Bowman, Costas, & Larivière, in preparation). Thus, a significant share of Twitter activity is assumed to reference the preprint version in the repository rather than the published version in the journal of record (Haustein, Bowman, Macaluso, Sugimoto & Larivière, 2014). Hence, repositories may be in an especially advantageous position to use altmetrics, however, altmetrics are not widely provided by repositories yet. Studies from Germany, Austria and Switzerland have shown that out of 173 investigated repositories only one offered altmetrics as a value added service (Kindling & Vierkant, 2014). This is likely to change as new tools and new services are being opened to help repositories integrate altmetrics. This chapter will provide an overview of various social media metrics and discuss possibilities and challenges in applying them in the context of online repositories.
Making Institutional Repositories Work